Search for the production of single vector-like and excited quarks in the Wt final state in pp collisions at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Journal of high energy physics, 2016)
A search for vector-like quarks and excited quarks in events containing a top quark and a W boson in the final state is reported here. The search is based on 20.3 fb−1 of proton-proton collision data taken at the LHC at a centre-of-mass energy of 8 TeV recorded by the ATLAS detector. Events with one or two leptons, and one, two or three jets are selected with the additional requirement that at least one jet contains a b-quark. Single-lepton events are also required to contain at least one large-radius jet from the hadronic decay of a high-pT W boson or a top quark. No significant excess over the expected background is observed and upper limits on the cross-section times branching ratio for different vector-like quark and excited-quark model masses are derived. For the excited-quark production and decay to Wt with unit couplings, quarks with masses below 1500 GeV are excluded and coupling-dependent limits are set.
*The ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 29.06.2020